(3GdeTjNI GdcHQi GdeNQLg ef eSehYGJ fLjH GdOjf CHj GdaQL YHO GddWja Hf YHO GdefYe Hf Ydi GdMQGfis - (3CMeO Hf eMeO Hf YHO Gddg, GHf GdXGgQjs
(3ChdgG (B:s
(3GdTjN GdChd fLjH CHh GdaQL YHO GddWja Hf YHO GdefYe Hf Ydi s
(3BNQgG (B:s
(3hdOJ HfJ GdWhjQ hJhajJ ai djdI GdSHJ dCQHYI YTQ djdI eVJ ef TgQ QHjY GdChd ef (B605 (3g` HHZOGO BNQ GdLRAGdQGHY YTQ s
(3GdfSNI HgG MhGTs
(3YdjgG bQGAGJ hSeGYGJ cKjQI ai ChdgG hBNQgG hCKfGFgGs
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs